SARS-CoV-2 delta (B.1.617.2) spike protein adjuvanted with Alum-3M-052 enhances antibody production and neutralization ability - Hong Huang; Zhongcheng Zhou; Xinxin Xiong; Zhihai Liu; Xiaoxue Zheng; Qingli Quan; Meixing Yu (Frontiers Media S.A., 2023)
BackgroundOptimizing adjuvant is one of the critical methods to improve the vaccine. 3M-052, a novel TLR7/8 agonist which was designed for slow dissemination at the injection site, has a potential as adjuvant, but its performance as a vaccine adjuvant for SARS-CoV-2 (B.1.617.2) spike protein has not been studied. The present study aimed to evaluate the effect of Alum-3M-052 as an adjuvant to improve mice serum antibody titers and pseudovirus neutralization efficiency.MethodFemale Balb/c mice were immunized 3 times at day 0, 7 and 21 intramuscularly with SARS-CoV-2 (B.1.617.2) spike protein and adjuvant (Alum or Alum-3M-052). Mice serum was collected weekly since day 7. Antibody titers of mice serum anti-SARS-CoV-2 (B.1.617.2) IgG and IgM were detected by ELISA. Inhibition rates of mice serum blocking SARS-CoV-2 (B.1.617.2) spike protein binding to ACE2 were detected by SARS-CoV-2 (B.1.617.2) Inhibitor Screening Kit. Neutralization efficiencies of mice serum against both SARS-CoV-2 (BA.2.12.1) pseudovirus and SARS-CoV-2 (B.1.617.2) pseudovirus were detected by pseudovirus neutralizing assay.ResultSerum of mice immunized by SARS-CoV-2 (B.1.617.2) spike protein adjuvanted with Alum-3M-052 had highest antibody titers and higher neutralization efficiency against both SARS-CoV-2 (BA.2.12.1) pseudovirus and SARS-CoV-2 (B.1.617.2) pseudovirus. Besides, neutralization efficiency of anti-SARS-CoV-2 (B.1.617.2) spike protein antibody against SARS-CoV-2 (BA.2.12.1) pseudovirus was lower than that of SARS-CoV-2 (B.1.617.2) pseudovirus.ConclusionAlum-3M-052 rapidly increased the titer of anti-SARS-CoV-2 (B.1.617.2) spike protein neutralizing antibodies and enhanced the neutralization ability against pseudoviruses and variants. This study provided evidence for the application of Alum-3M-052 as an adjuvant in COVID-19 vaccines production.